Increasing Organizational Capabilities of PAUD Units Through the Digital Leadership Seminar - Tepi Mulyaniapi; Johar Permana; Soemarto; Diding Nurdin (Universitas Lancang Kuning, 2023)
Improving the capabilities of Early Childhood Education (PAUD) organizations is crucial for efficient and effective management. A well-developed organizational capability can also help enhance public trust in PAUD programs. This is important because public trust ensures ongoing support and access to resources needed for the successful operation of PAUD programs. However, limitations in resources and the ability to leverage technology can pose challenges in enhancing the effectiveness and efficiency of PAUD institutions. The goal of this community service initiative is to enhance understanding of the role of technology in education, develop digital leadership skills, and improve collaboration and communication among PAUD leaders throughout West Java. The main activity of this community service initiative is a Digital Leadership seminar. Through this community service initiative, it is expected that the capabilities of PAUD institutions will be enhanced. . Keywords: Capability, Organization, Leadership, Digital Leadership